2018
DOI: 10.1111/1750-3841.14067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Expectation Measure on the Sensory Acceptance of Petit Suisse Product

Abstract: This study generated a significant contribution, especially for companies that aim for a wider market. The application of sensory analysis with a focus on expectation measure, it shows that the brand determines the purchase, based on the results of this study. Therefore, the product's visual identity must be invested in; it must arouse children and adults' attention. That is, it reinforces that the image of the product, the label and what it arouses in the consumers are extremely important for the final choice. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…These results open a market possibility to be explored, which includes consumption of Petit-Suisse cheese also by adults. In the study by Lopes et al (2018), with adults ranging from 18 to 25 years, only 20% of the respondents consumed the product monthly. In France, Petit-Suisse cheese is available as a white cheese option, without the addition of fruit or sugar preparations, and the frequency of consumption of this type of product is on average once a week by 31% of adults (Cesbron-Lavau et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results open a market possibility to be explored, which includes consumption of Petit-Suisse cheese also by adults. In the study by Lopes et al (2018), with adults ranging from 18 to 25 years, only 20% of the respondents consumed the product monthly. In France, Petit-Suisse cheese is available as a white cheese option, without the addition of fruit or sugar preparations, and the frequency of consumption of this type of product is on average once a week by 31% of adults (Cesbron-Lavau et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, one of the five most produced cheeses is Petit-Suisse cheese. This is one of the greatest growing cheeses between 2007 and 2011, reaching 54.5 thousand tons, an increase of 102.1% (Lopes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that perceived quality is not the same as expected quality [35]. Branding has a significant impact on consumer hedonic scores [36], and it has been shown that altering packaging information and other external cues can affect sensory perception [37] and influence consumer decisions [38]. Therefore, by positively marketing these differences to the UK consumer as the products' unique selling point prior to launching such a product into the UK market, one could moderate the consumer expectation and consequently improve the sentiment towards the appearance of Blaas A and B.…”
Section: The Impact Of Cultural Differences On Liking For Waterford Blaamentioning
confidence: 99%
“…Factors, such as sensory characteristics, psychological influences due to past experiences, product information, cognitive factors and marketing strategies, influence perception of food products. These factors often create expectations (before tasting the product) that can sway consumer's perception of a product when they are confirmed and disconfirmed (after tasting the product) (Delwiche, ; Hurling & Shepherd, ; Teixeira Lopes, Passos Rodrigues, & Souza de Araújo, ; Urbanus, Schmidt, & Lee, ; Wan, Woods, Seoul, Butcher, & Spence, ).…”
Section: Introductionmentioning
confidence: 99%